Long‐term evaluation of respiratory status after esophageal atresia repair1. Issue 2 (22nd May 2012) - Beucher, J.; Wagnon, J.; Daniel, V.; Habonimana, E.; Fremond, B.; Lapostolle, C.; Guillot, S.; Azzis, O.; Dabadie, A.; Deneuville, E.
Abstract Rationale Esophageal atresia (EA) is a congenital malformation. Nowadays, its initial prognosis is excellent thanks to improvements in neonatal and surgical management. However, the assessment of long‐term respiratory outcome has become necessary in affected children and was thus performed in this study. The benefits of cardiopulmonary function testing were also examined. Methods The medical records of 77 children operated on for EA between 1990 and 2004 were reviewed. The results of respiratory function testing and cardiopulmonary response to effort were collected, together with neonatal and anthropometric data. Results Acceptable measurements were obtained in 31 children with EA. These children were comparable to the ones lost during follow‐up. The results of pulmonary function tests (PFTs) were abnormal in 21 cases (68%). A poor ventilatory response was detected in 14 children (45%) by cardiopulmonary function testing. Ten children who had abnormal results on PFTs were not under any anti‐asthmatic treatment. Conclusions Impaired lung function was noted in children with repaired EA. Indeed, cardiopulmonary function tests results correlated with standard spirometric parameters and revealed minimal clinical symptoms. Moreover, many children with EA had a limited ventilatory reserve (VR). These results indicate that respiratory symptoms are often neglected in children with repaired EA and reinforce the need to provide adequate treatment. Pediatr Pulmonol. 2013; 48:188–194. © 2012 Wiley Periodicals, Inc.